Comparing Negative Emotional Components in Older People With Normal and Poor Quality of Sleep - Mobarekeh Ansari; Behruz Doulatshahi; Rabab Sahaf (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives: Sleep is one of the basic needs of every human being. Considering the factors affecting this area is of particular importance. The present study compares the negative emotional components, including rumination, worry, arousal anxiety in older people with sleep problems, and those with normal sleep.  Methods & Materials: This research is a causal-comparative study. The study population consisted of older people living in Tehran City in 2016. The study samples were selected by the convenience sampling method and based on inclusion and exclusion criteria. The inclusion criteria included being ≥60 years old, lacking severe illnesses and disorders (whether physical and psychological). The exclusion criterion included the unwillingness to continue study at each stage. Of 200 older people participating in the study, 131 individuals were included in the study after group matching based on demographic variables. Pittsburgh sleep quality index, ruminative responses scale questionnaire, Pennsylvania state worry questionnaire, mood and anxiety symptom questionnaire, and anxious arousal scale were used to collect the study data. The reliability of the tools was also evaluated. The obtained data were analyzed by descriptive statistics of frequency, mean and by inferential statistics of the Chi-square, Man-Whitney U, and Independent t test in SPSS V. 18. Results: The Mean±SD age of the subjects was 68.5±6.78 years, respectively. The mean scores of rumination were 54.039 in the elderly group with poor sleep quality and 44.919 in the group with normal sleep quality. Also, the mean scores of worry were 53.875 and 46.024 in the poor and normal sleep quality group, respectively. Finally, the mean arousal anxiety scores were 55.080 and 43.772 in the poor and normal sleep quality group, respectively. There was a statistically significant difference between the mean values of the two groups in terms of research variables (P<0.001). Conclusion: According to the study results, rumination, worry, and arousal anxiety have a negative effect on the quality of sleep. Focusing on these negative emotional components as risk factors for the emergence and continuation of sleep disturbances can be useful in designing preventive interventions for sleep problems and reducing psychological disorders.